PENGEMBANGAN LEMBAR KERJA MAHASISWA (LKM) BERBASIS INQUIRI PADA MATA KULIAH STRATEGI PEMBELAJARAN KIMIA - Erviyenni '; Sri Haryati (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2016)
Research of development that held to produce student worksheet (SWS) based on valid inquiry, practice, and effective to complete courses of chemistry learning strategy. The method that used is research of development. The research used consists of four steps, namely define, design, develop, and disseminate, because the limit of time and cost, research just used until to development step. Data of research collected through evaluation sheets filled by validator. Internal validation of SWS describe that SWS writing contain indicators assessment, writing use capital letters, the distance between topic letter with information letter was different, but still used more than 10 words in line. For contain assessment can used by students with various understanding, yet include steps to find, but give various activities (read, discuss, and answer). SWS give opportunities to find different information because instruction that used in exercise requires students to read paper and another book. This activity can develop social and emotional relation, because students werediscuss in their group. Language that used has same with intellectual level of students. Format assessment describe that SWS have a title, purpose, resume, work steps, questions and include reference, also table. It requires students to implement the examples in learning activity.